2013
DOI: 10.5513/jcea01/14.2.1273
|View full text |Cite
|
Sign up to set email alerts
|

Body conformation and morphometry of some internal organs of Pharaoh quail of different ages

Abstract: The effect of age of Pharaoh quail on body weight, body conformation and development of internal organs, including the digestive tract, was determined. At the age of 35 days, Pharaoh quail were characterized by significantly lower body weight, length of trunk with neck, and length of trunk compared to 45-day-old birds. Younger quail had slightly shorter breast bone and lower thighs, smaller chest girth, and the same length of shanks. Body conformation indices were significantly (P0.05) higher in 35-day-old bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
1
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 13 publications
1
1
3
Order By: Relevance
“…This value was reported as 3.7 cm for five-week-old animals by Wilkanowska et al (2013) and as 3.93 cm for six-week-old animals by Momoh et al (2014). The results of the present study demonstrated that the shank length of five-week-old quail chicks ranged between 33.94-34.63 mm in females and between 33.44-34.10 mm in males.…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…This value was reported as 3.7 cm for five-week-old animals by Wilkanowska et al (2013) and as 3.93 cm for six-week-old animals by Momoh et al (2014). The results of the present study demonstrated that the shank length of five-week-old quail chicks ranged between 33.94-34.63 mm in females and between 33.44-34.10 mm in males.…”
Section: Discussionsupporting
confidence: 56%
“…mean intestine length determined in this study was similar to that reported by Wilkanowska et al (2013) for five-weekold Japanese quails (73.3 cm), this value was higher than that reported by Hassan et al (2015) for six-week-old animals (54.86 cm). Furthermore, the total length (63.44 cm) of the small (55.6 cm) and large (7.84 cm) intestines and the intestine weight (5.35 g) reported by Hena et al (2012); the total length (56.41) of the small (50.02 cm) and large (6.39 cm) intestines and the intestine weight (3.86 g) reported by Guluwa et al (2014); and the total intestine length (61.93 cm) and intestine weight (7.69 g) reported by Samadi and Sahneh (2015) were lower than the results obtained in the present study.…”
Section: Discussioncontrasting
confidence: 42%
“…Carcass yield values in our study were higher than the ones recorded with the control and in various quail species, including Pharaoh quails at 35 and 42 days by Wilkanowska et al [ 34 ], meadow quails at 49 days by Vali [ 35 ],and Japanese quails between 35 and 56 days [ 35 – 37 ]. Furthermore, our values are close to those reported by Djitie et al [ 19 ] for quails in the West Cameroon highlands and Seyed-Alireza et al [ 38 ] for Japanese quails.…”
Section: Discussioncontrasting
confidence: 76%
“…The testicular weight noted with the control treatment is higher than those observed by Vatsalya and Kashmiri[ 45 ], but those obtained with the T2 treatment (30%) at 56 days are higher than the latter and those obtained by Wilkanowska et al [ 34 ] on Pharaoh quails. This can be justified by the fact that the latter’s readings were taken on animals younger than ours, as testicular weights and volumes generally increase with age until puberty and reach maximum values at the sexual period [ 9 , 46 ].…”
Section: Discussioncontrasting
confidence: 50%
“…In their study on Japanese quails (Coturnix japonica), Ojo et al (2014) reported 2.96 cm and 2.95 cm leg lengths in 4-weekold females and males, respectively, and indicated that leg length increased to 3.00 cm at 6 weeks of age in both sexes. Wilkanowska et al (2013) reported equal leg length (3.7 cm) in 35-day-old and 45-dayold female and male quails, whereas Gambo et al (2014) determined and average leg length of 3.21 cm in 5-week-old quails.…”
Section: Selected Traits Of Hatched and Unhatched Eggs And Growth Permentioning
confidence: 96%